Parental resources and heritability as factors shaping children's health. An analysis of twins' self-rated health using TwinLife - Holzwarth, Bärbel; Wolf, Christof (Frontiers in Sociology, 2023)
We assess the relative and joint contributions of genetic and environmental factors on health during childhood and assume that parental resources are part of the environmental factors shaping children’s health. We discuss theoretical background and empirical evidence concerning the effects of parental resources and heritability on children’s health. Based on these findings we formulate six hypotheses guiding our empirical analysis, using data from TwinLife, a nationally representative sample of same sex twin pairs in Germany. We analyze self-rated health of 1,584 twin pairs aged 4 to 18. We did find strong support for the idea that parental resources influence children’s health: household income and fathers’ education consistently show positive effects. In contrast to our expectation, we did not find that genetic factors influence the health of well-off children less than the health of children living in families with lower SES. We also did not find that the genetic influence on health increases during childhood and adolescence. On the contrary our results indicate that the role played by genetic factors diminishes whereas environmental factors gain importance for health of children while growing up. This finding is good news for those interested in improving health chances of children from lower SES backgrounds because it demonstrates the malleability of children’s health.